Blood coagulation time in response to simulated trawling and recovery time of wild Atlantic Cod (Gadus morhua L.) - Tichy, Jakub (UiT The Arctic University of Norway, 2015)
Wild Atlantic cod (Gadus morhua L.) was used to assess possible effects of different treatments on blood coagulation time, fillet redness and possible correlationship between blood coagulation time and fillet redness by simulating fish capturing and handling activities. During blood coagulation time assessment fish were tested for different treatments simulating commercial fishing operations. Three different treatments were tested – exhaustive exercise represented by swimming in experimental swimming tunnel, packing in experimental cod-end for two different time periods, recovery in recovery containers for three different time periods. Combination of treatments divided tested fish into eight groups in order to be able to assess the influence of each treatment separately.